SEJARAH SASTRA ARAB DI ANDALUSIA - Nur Hidayah (CMES (Center of Middle Eastern Studies), 2013)
Arabic literature in Andalusia is a part of the enriching presence of Arab literature in Middle East. Geographically, Andalusia is located in Europe. Arabic literature comesinto Europe by Futuhat Islamiyah. Color and pattern in Arabic Andalusian literary,which became known as the Arab Maghreb Literature - opponent of Arabic literatureMasyriq - very different from the forms of Arabic literature in the Middle East. Kind of acomplex society and Andalusia are from different races and religions with beautifulnatural conditions and rich powerful influence for Arabic literature. So that the writerscreate works that are creative, beautiful, with high imagination and choice of words areeasy to understand. Many emerging new literary genres that are not known in Masyriqlike Mala Luzum Yalzam , Muwasyah or Mu'aradhah. Many literary works are timelessand be a reference to the works of modern literature in the world. Like Hayy bin YaqdzanIbnu Thufail or Thouqul Hamamah Ibn Hazm Al-Andalusia.Arabic literature in Andalusia is a part of the enriching presence of Arab literature in Middle East. Geographically, Andalusia is located in Europe. Arabic literature comesinto Europe by Futuhat Islamiyah. Color and pattern in Arabic Andalusian literary,which became known as the Arab Maghreb Literature - opponent of Arabic literatureMasyriq - very different from the forms of Arabic literature in the Middle East. Kind of acomplex society and Andalusia are from different races and religions with beautifulnatural conditions and rich powerful influence for Arabic literature. So that the writerscreate works that are creative, beautiful, with high imagination and choice of words areeasy to understand. Many emerging new literary genres that are not known in Masyriqlike Mala Luzum Yalzam , Muwasyah or Mu'aradhah. Many literary works are timelessand be a reference to the works of modern literature in the world. Like Hayy bin YaqdzanIbnu Thufail or Thouqul Hamamah Ibn Hazm Al-Andalusia.